2015
DOI: 10.1002/pc.23879
|View full text |Cite
|
Sign up to set email alerts
|

Development of basalt fiber‐reinforced thermoplastic composites and effect of PE‐g‐MA on composites

Abstract: The thermoplastic matrix composites have gained great importance in last three decades. The chopped basalt fiber (mineral fiber) is considered to be a good fiber due to excellent properties as potential reinforcement of composite materials. In this work, composites of chopped basalt fiber (6 mm) with thermoplastic material Nylon-6(Polyamide-6) were prepared and its mechanical and morphological properties were evaluated for automobile applications. The melt blending was carried out in corotating twin-screw extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, the manufacturing process of BFs is similar to that of glass fibers. BFs have been used within studies as reinforcements in thermoplastic matrices in the last years [15,16]; however, the usage in WPCs as reinforcement was rarely reported. Chen et al [17] added BFs into a commercial WPC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the manufacturing process of BFs is similar to that of glass fibers. BFs have been used within studies as reinforcements in thermoplastic matrices in the last years [15,16]; however, the usage in WPCs as reinforcement was rarely reported. Chen et al [17] added BFs into a commercial WPC.…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation for the blend containing PE-g-MA at 2.5 is also lower when compared to the blend containing PE-g-MA at 5.0. Prajapati et al (2017) carried out a study using PE-g-MA as a coupling agent in composites of PA6 reinforced with basalt fiber and verified that the MP obtained by tensile and impact testing have improved and relatively remain stable when the PE-g-MA is incorporated to the composites at 3 to 5 wt%. Thus, the results of Prajapati et al (2017) as well as the results of this present study lead to the conclusion that the PE-g-MA incorporated at ~3 wt% in blends or composites of PA6 is effective for the compatibilization of these materials.…”
Section: Mpmentioning
confidence: 84%
“…Thus concluded that maleic anhydride helps in enhancing the interaction between the BF and PP. Prajapati et al [ 10 ] reinforced nylon with BF and concluded that the coupling agent modified composites had better mechanical properties. Enhanced interfacial adhesion and reduced fiber breaking increased the properties of the composites.…”
Section: Introductionmentioning
confidence: 99%